OVERVIEW OF BLOCKCHAIN TECHNOLOGY USE IN EDUCATION AND SCIENCE - Vinnyk Максим; Poltorackiy Максим; Ilyina Інна (Journal of Information Technologies in Education (ITE), 2022)
This article presents a comprehensive overview of the application of blockchain technology in education and science, analyzing its potential as a key innovation in the digital economy. The fundamental properties of blockchain security, transparency, decentralization, and data immutability are emphasized as enablers for the modernization of educational processes, the elimination of intermediaries, and the enhancement of digital trust in the context of global mobility. The study reviews existing academic literature on blockchain implementation in educational settings and examines international experiences of its adoption. Particular attention is paid to practical examples of how universities worldwide are utilizing blockchain to support educational and scientific activities, as well as to optimize business processes. As a disruptive technology, blockchain provides tools for equipping the digital society with technological mechanisms to verify the authenticity of transactions, establish digital identities, and record and improve educational processes. The global education sector is evolving rapidly, and the growing adoption of blockchain reflects an increasing demand for higher levels of digital trust, which constitutes both the value and the future potential of this technology. The analysis reveals the accelerated pace of development and the expanding circle of blockchain proponents. To foster a deeper understanding, the article presents an operational mechanism of the technology following the review of implementation cases, offers analogies, systematizes advantages and disadvantages, and outlines the main areas of application. One of the most promising directions identified is the tokenization of education, which can bridge existing gaps in the educational services market, digital transformation, and blockchain technologies. In conclusion, the article highlights blockchain’s potential to transform educational data management, assessment, and documentation workflows, offering an alternative to traditional approaches, especially in distance learning contexts. Despite being at an early stage of integration, the impact of blockchain continues to grow. Future research aims to develop a model for an educational online platform based on tokenization. The platform is intended to foster collaboration, enhance motivation, and create an effective crypto-ecosystem for learning and investing in educational initiatives. This article contributes to the ongoing discourse on the systemic integration of blockchain and tokenomics into educational practice.